2000
DOI: 10.1007/s11745-000-0586-y
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid supplementation in humans: Effects on circulating leptin concentrations and appetite

Abstract: Conjugated linoleic acid (CLA) has been demonstrated to reduce body fat in animals. However, the mechanism by which this reduction occurs is unknown. Leptin may mediate the effect of CLA to decrease body fat. We assessed the effects of 64 d of CLA supplementation (3 g/d) on circulating leptin, insulin, glucose, and lactate concentrations in healthy women. Appetite was assessed as a physiological correlate of changes in circulating leptin levels. Analysis of plasma leptin concentrations adjusted for adiposity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
98
6
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 36 publications
14
98
6
6
Order By: Relevance
“…In our experiment, there was no effect of any treatment on serum leptin concentration. Dietary CLA reduced serum leptin levels in rats, mice and humans (Delany et al, 1999;Medina et al, 2000;Yamasaki et al, 2000b), whereas it was increased in lactating sows (Bontempo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, there was no effect of any treatment on serum leptin concentration. Dietary CLA reduced serum leptin levels in rats, mice and humans (Delany et al, 1999;Medina et al, 2000;Yamasaki et al, 2000b), whereas it was increased in lactating sows (Bontempo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…31,102,[107][108][109][110][111] The effect of CLA on insulin sensitivity and glucose control are also inconsistent. 28,29,93,114,116,126 In conclusion, most existing evidence of CLA efficacy on adiposity stems from animal studies, particularly those conducted in mice. The majority of these animal studies have examined CLA mixtures but not individual isomers for weight and fat-lowering properties.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin and glucose levels remained unaffected. 126 In type II diabetes subjects, CLA supplementation was associated with increases of fasting plasma glucose concentration; correlation analyses showed that plasma levels of the t10c12, but not the c9t11, CLA isomer was inversely associated with serum leptin. 121 Supplementation with t10c12 CLA caused isomer-specific insulin resistance in obese men with the metabolic syndrome.…”
Section: Cla and Human Body Weight And Compositionmentioning
confidence: 95%
“…However, it also constitutes a limitation in that it prevents the direct extrapolation of these results to other species. Given that CLAmediated increases in plasma insulin levels and insulin resistance have been reported in humans [7,30], the effect of CLA on insulin homeostasis may not be restricted to the mouse. Furthermore, if the early and profound decreases in leptin and adiponectin levels documented here in CLA-fed mice also occur in humans, this could have deleterious consequences for whole body insulin sensitivity and favour the development of fatty liver.…”
Section: Discussionmentioning
confidence: 99%